XIX a. pirmosios pusės knygų prekybos Didžiojoje Lietuvoje istorijos šaltiniai - Navickienė, Aušra (Knygotyra, 1995)
An origin of the sources about book trade during 1795–1864 in Great Lithuania was mainly this: 1) activity of individual book publishing and selling enterprises and persons; 2) activy of public institutions which had direct or undirect links with book publishing and distribution; 3) administrative activity of state and its intervention in book publishing and distribution. The object of research is 585 Lithuanian books, published by characteristic for feudalism enterprises, institutions and private booksellers, printers who replaced them and were very important sources of book trade at the same time. Very helpful is information which we can find in the books (lists of subscribers and information lists of books trade) and occuring marginalias. They inform about an assortiment of lithuanian books and their buyers. A little group of sources consists of books trade catalogues and archival documents of individual book trade enterprises. The archives of J. Zavadzkis firm has remained intact and is kept in LVIA. It is especially important for unique material about selling of lithuanian books. Rather plentiful published and unpublished correspondence and memoirs of booksellers, enterprises and establishments help us to clear up the circumstances of distribution of separate publications, circle of unskilled booksellers, their relationship. Arising of new public publishing companies and organizations publishing and distributing lithuanian books was not charasteristic because of very difficult lithuanian language situation in the 19th century public life. Only few archival documents of their activity have remained infact till nowadays. A new source for studying lithuanian books trade is periodical press – which fills in the gaps. Various messages about books distribution and news of books were published there. Major group of sources was created by active state work in administration, fight against lithuanian political-cultural peculiarity, in organization of tax collecting and public education. The documents of Vilnius magistracy (later Duma), Vilnius governorgeneral, civil governor, police-master offices, Vilnius censorship committee inform us about the juridical foundation of books trade, its control and help us to clear up persons and enterprices engaged in book trade, forms of their activity and their expenses. Next to unpublished documents another group of sources consists of law publication and statistical, informative collections which had their beginning in the 19th century.